2017
DOI: 10.1002/cphc.201700972
|View full text |Cite
|
Sign up to set email alerts
|

Band‐Gap Engineering of Graphene Heterostructures by Substitutional Doping with B3N3

Abstract: We investigated the energetics and electronic structure of B N -doped graphene employing density functional theory calculations with the generalized gradient approximation. Our calculations reveal that all of the B N -doped graphene structures are semiconducting, irrespective of the periodicity of the B N embedded into the graphene network. This is in contrast to graphene nanomeshes, which are either semiconductors or metals depending on the mesh arrangement. In B N -doped graphene, the effective masses for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It has an antiferromagnetic ground state with a direct band gap of 1.41 eV, indicating the feasibility of applying the B 3 N 3 ring as a unit to construct semiconductor material . Furthermore, the substitution of B 3 N 3 in graphene and its analogue have been investigated by means of experiments and DFT simulation, resulting in an enlarged band gap and obvious shift of optical adsorption to the ultraviolet region . Inspired by the above studies, it could be hypothesized that replacing benzene ring by the B 3 N 3 ring in π-conjugated metal bis­(dithiolene) nanosheets is probably a feasible strategy to regulate the band structure and light utilization efficiency, enhancing its photoactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It has an antiferromagnetic ground state with a direct band gap of 1.41 eV, indicating the feasibility of applying the B 3 N 3 ring as a unit to construct semiconductor material . Furthermore, the substitution of B 3 N 3 in graphene and its analogue have been investigated by means of experiments and DFT simulation, resulting in an enlarged band gap and obvious shift of optical adsorption to the ultraviolet region . Inspired by the above studies, it could be hypothesized that replacing benzene ring by the B 3 N 3 ring in π-conjugated metal bis­(dithiolene) nanosheets is probably a feasible strategy to regulate the band structure and light utilization efficiency, enhancing its photoactivity.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In addition, covalent chemistry facilitates an easy and effective route to band-gap structure modulation in graphene. 5−7 Tuning the electronic energy gap by band gap engineering is a growing area of materials chemistry, 8,9 and it is found that, in a graphene-like platform, such tunability can be achieved even with singleatom-level doping. 10−12 The introduction of electronegative atoms such as fluorine in the honeycomb lattice of graphene is one way of modulating the band gap, although precise quantitative relationships between the electronic structure of the dopant atom, stoichiometry, and its exact placement in the graphene structure have not been clearly deciphered yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, the zero band gap of graphene poses a challenge in the design of devices with on and off switching of electrical currents . The electronic band gap is the energy difference between the valence and conduction bands in a semiconductor, which manifests an inverse relationship to the carrier mobility, and hence an increase in the band gap of graphene can modulate its carrier mobility and improve its applicability in sensor platforms. , In addition, covalent chemistry facilitates an easy and effective route to band-gap structure modulation in graphene. Tuning the electronic energy gap by band gap engineering is a growing area of materials chemistry, , and it is found that, in a graphene-like platform, such tunability can be achieved even with single-atom-level doping. …”
Section: Introductionmentioning
confidence: 99%
“…Even though the F atoms are only attached to particular sublattices, the fluorinated graphene no longer possesses the Dirac cone but massive valleys for both conduction and valence band edges when the graphitic region does not satisfy the resonant condition of aromaticity, as is the case of graphene with periodic vacancies [27,28]. Substitutional doping of a borazine skeleton into graphene opens the finite band gap, which depends not only on the BN ring concentration but also on their mutual BN ring arrangements in the graphene network [29]. N-doped graphene also exhibits unusual electronic properties, which depend on the local and global atomic arrangements, and is applicable to electronic and catalytic devices [30,31,32,33,34,35,36,37,38,39,40].…”
Section: Introductionmentioning
confidence: 99%